(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Most patients with acute appendicitis can be easily diagnosed, but there are many in whom the signs and symptoms are quite variable, and a firm clinical diagnosis is often very difficult to establish. Difficulties in the early diagnosis of appendicitis, particularly in children, often lead to life threatening complications, such as gangrene or perforation of the appendix. Here we report a case where a nine-year-old boy presented to the Paediatric Department at Anwer Khan Modern Medical College Hospital in Dhaka in April 2016 with a history of abdominal pain, vomiting & fever that began nine days before admission. Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 73-75